Enhancing the effectiveness of FSPPP’s Graduate Researchers in Print (GRiP) through a holistic and comprehensive research ecosystem framework: a pathway to promote research excellence among postgraduate students / Yarina Ahmad and Posiah Mohd Isa - Ahmad, Yarina; Mohd Isa, Posiah
FSPPP’s Graduate Researchers in Print (GRiP) is a program designed to support research students in their academic writing, particularly thesis writing. This program is an emulation of the GRiP program introduced by the Faculty of Arts, Monash University, Australia. At present, the GRiP program is widely implemented in many Australian universities as it has been proven to be effective in assisting research students in their thesis writing and research completion. The FSPPP-GRiP program has been officially implemented since 10th March 2016, with a number of 16 participants: 8 Master and 8 Ph.D. students. After six months of the program implementation, the participants were interviewed to gather their feedback regarding the program’s effectiveness at three different levels: individual level, peer support and assistance from the GRiP’s coordinator. The findings of this study reveal that the participants have marked significant improvement at the individual level which can be seen from their academic writing (amount, quality, and improvement in writing skills and techniques), which has increased their study commitment, improved their communication repertoire alongside acted as a driving factor in propelling the participants to complete their study on time. The effectiveness of the GRiP program can also be seen from the peer support level. Peers and their research progress are recognized as benchmarks for other GRiP participants. They learn from each other’s experiences (process and procedures, formatting, referencing, style of writing, writing techniques and structure), as well as obtaining support and motivation to complete their study. Learning from peers has made them feel less stressful and lonely in conducting their research. Notably, the role of the GRiP coordinator is prominently effective in facilitating discussions among GRiP participants, verifying the information and feedback from the participants, advising the participants about process and procedures and continuously support and motivate the participants to produce a sound thesis and complete their studies on time. This study concludes that the effectiveness of the GRiP program can be seen from individual, peer and coordinator levels. To further enhance research culture among students at the faculty, a holistic framework of the GRiP ecosystem is proposed. To excel in research, all parties have pertinent roles in assisting and supporting research students in their research journey—this can only be achieved through a holistic and comprehensive research ecosystem framework as proposed in this study.